The Efficacy of Triptolide in Preventing Diabetic Kidney Diseases: A Systematic Review and Meta-Analysis - Liang, Dongning; Mai, Hanwen; Ruan, Fangyi; Fu, Haiyan (Frontiers in Pharmacology, 2021)
Ethnopharmacological relevance: Triptolide (TP), the primary biologically active ingredient of Tripterygium Wilfordii Hook F. (TWHF), possesses the potentials to solve the shortcoming of TWHF in treating diabetic kidney diseases (DKD) in the clinic. Aim of the study: We conducted a meta-analysis to evaluate the efficacy of TP in treating DKD and offer solid evidence for the further clinical application of TP. Materials and methods: Eight databases (CNKI, VIP, CBM, WanFang, PubMed, Web of Science, EMBASE, and Cochrane library) were electronically searched for eligible studies up to October 17, 2020. We selected Animal experimental studies using TP versus Renin-angiotensin system inhibitors or nonfunctional liquid to treat DKD by following the inclusion and exclusion criteria. Two researchers independently extracted data of the included studies and assessed risk of bias with the Systematic Review Centre for Laboratory Animal Experimentation Risk of Bias tool. Fix effects meta-analyses, subgroup analyses and meta-regression were conducted with Rev Man 5.3 software. Inplasy registration number: INPLASY2020100042. Results: Twenty-six studies were included. Meta-analysis showed that TP significantly reduced albuminuria (14 studies; standardized mean differences [SMD]:-1.44 [–1.65, −1.23], I2 = 87%), urine albumin/urine creatinine ratio (UACR)(8 studies; SMD:–5.03 [–5.74, −4.33], I2 = 84%), total proteinuria (4 studies; SMD:–3.12 [–3.75, −2.49], I2 = 0%), serum creatinine (18 studies; SMD:–0.30 [–0.49, −0.12], I2 = 76%), and blood urea nitrogen (12 studies; SMD:–0.40 [–0.60, −0.20], I2 = 55%) in DKD animals, compared to the vehicles. However, comparing TP to the renin-angiotensin system (RAS) inhibitors in DKD treatment, there was no marked difference in ameliorating albuminuria (3 studies; SMD:–0.35 [–0.72, 0.02], I2 = 41%), serum creatinine (3 studies; SMD:–0.07 [–0.62, 0.48], I2 = 10%), and blood urea nitrogen (2 studies; SMD:–0.35 [–0.97, 0.28], I2 = 0%). Of note, TP exhibited higher capacities in reducing UACR (2 studies; SMD:–0.66 [–1.31, −0.01], I2 = 0%) and totoal proteinuria (2 studies; SMD:–1.18 [–1.86, −2049], I2 = 0%). Meta-regression implicated that the efficacy of TP in reducing DKD albuminuria was associated with the applied dosages. In addition, the publication bias has not been detected on attenuating albuminuria between TP and RAS inhibitors after DKD.